Aplikasi Electronic Customer Relationship Management (E-CRM) untuk Meningkatkan Layanan Orang Tua pada Madrasah Aliyah Al-Falah - Fadil Muhammad Zuhri; Safitri Juanita (Universitas Wahid Hasyim, 2024)
Competition between private schools in New Student Admissions (PSB) requires the right strategy, namely implementing Electronic Customer Relationship Management (E-CRM). Madrasah Aliyah (MA) Al-Falah is currently having a problem with decreasing the number of prospective new students (CSB) during the pandemic because the CSB registration process is carried out offline, and brochures are distributed when CSB comes to school. Apart from that, there is no media for alumni to provide positive reviews or for students' parents to give criticism and suggestions. Therefore, this research contributes to designing an E-CRM application to increase the number of CSB and student-parent services at MA Al-Falah. This research aims to simplify the CSB admission process by implementing two stages of CRM, namely acquiring and retaining, to increase the loyalty of parents so that their children return to school at MA Al-Falah and provide solutions in terms of school promotions, alumni reviews, and criticism of suggestions from students' parents. The method used in this research is qualitative research with descriptive analysis and the Waterfall system development method. This research concludes that the E-CRM application at MA Al-Falah helps make the PSB process easier because it features a registration form, registration fee information and discount coupons. The E-CRM system can also increase the loyalty of students' parents because it has a suggestion and criticism feature.